The Relationship of Emotional Arousal with the Level of Acetyl Cholinesterase and Lactic Acid in Young Basketball Players - Hayder Naji Habash Alshawi (Journal of Global Pharma Technology, 2017)
The study of the relationship between emotional arousal and the enzyme acetyl cholinesterase in terms of (acid lactic acid) in young basketball players is of great importance which has played a large role in the direction of the researchers towards such a study. The problem of research was that the basketball game of games of relatively small space The researchers should study the effect of the enzyme acetylcholine in the emotional excitation and lactic acid to achieve the best results. The objectives of the research were to identify the level of emotional arousal, the enzyme acetyl cholinesterase and the level of lactic acid and the level of some of the effectors Physiological studies of young basketball players, and to identify the correlation between the level of emotional arousal and the enzyme acetylcholine acetate and lactic acid for young basketball players, the researchers used the descriptive method in a method of surveying and correlative studies to suit the nature of the problem, the players of the Middle and South Euphrates basketball players participating in The Premier League for the sports season 2016-2017, the nine clubs (Basrah, Maysan, Muthanna, Wasit, Dhiqar, Rafidain, Solidarity, Babylon and Karbala). The sample was selected in a simple random way, (20) players (10) for the Sports Solidarity Club and (10) for the Rafidain Sports Club. The researchers used the following tests: First: to measure the level of emotional arousal, second: biochemical variables, The concentration of lactic acid, measured the concentration of acetylcholine enzyme, and the researchers concluded the high level of emotional arousal of players as a result of the impact of psychological factor. Decreased action of the enzyme acetyl cholinesterase due to the concentration of lactic acid in the muscle, which leads to slow work and sending instructions Increase the proportion of lactic acid in the muscles as a result of the high level of emotional arousal and recommended the adoption of the results of research and use by basketball coaches to know the psychological effects of physiological basketball players. Attention to the psychological preparation of the players in the course of the training along with the physical numbers and skills and plans because of its importance in its reflection on the physical and physiological aspect and therefore on performance. To establish a department for sports medicine in faculties of physical education and sports sciences and provide all specialized devices in order to facilitate the task of conducting research and studies. Conduct research and similar studies by researchers to standardize and determine standard levels of emotional arousal scores on individual and group games.Keywords: Emotional arousal, Acetyl cholinesterase, Lactic acid and basketball.